Is there a relationship between spondyloarthritis and periodontitis? a case-control study (2017)
Objective To compare the frequency and severity of periodontitis in patients with spondyloarthritis (SpA) with healthy control individuals, through the evaluatio of clinical, serological and microbiological periodontal condition. Methods Patients with a diagnosis of SpA (n=78) and biological disease-modifying antirheumatic drug (bDMARD) naive fulfilling the Assessment of SpondyloArthritis international Society (ASAS) classification criteria as well as 156 healthy controls matched for age/gender were included. Two trained and calibrated periodontologists performed the periodontal clinical assessment. The presence of periodontitis and its severity were determined according to the criteria established by the Centers for Disease Control and Prevention-American Academy of Periodontology. The clinical periodontal variables, IgG1/IgG2 antibodies against Porphyromonas gingivalis andperiodontopathic bacterial identification, were also established. Comparisons of periodontal characteristics between the patients with SpA and the control group were performed using univariable analyses. A logistic regression analyses was performed to calculate the OR (95% CI) for diagnosis of periodontitis in patients with SpA and matched controls. Results A diagnosis of periodontitis was established in 56% in patients with SpA versus 69% of healthy controls (P≤ 0.01). Severe periodontitis was found in 3% versus 12% in SpA versus healthy controls, respectively (P≤ 0.01). There was no significant increase of frequency of any periodontal variable, IgG1/IgG2 antibodies against P. gingivalis or the presence of periodontopathic bacteria between patients with SpA and control group. Periodontitis was not positively associated with a diagnosis of SpA (OR: 0.57, 95% CI 0.32 to 1.00, P=0.05) in the logistic regression analyses. Conclusions We found a lower rather than a higher frequency and severity of periodontitis in patients with SpA in comparison with healthy control individuals. Our findings suggest that there is no positive association between SpA and periodontitis in Colombian patients.